Considerations about a new syndrome (AIDS) and blood transfusions or fractions and their impact on our environment - Ruiz Nieto, Eduardo (Revista Universidad de Guayaquil, 1984)
In August 1983, a news item appeared in the media of our country, which produced great expectations at all levels of the population, especially among homosexual individuals, to whom special reference was made in the news. On March 4, 1983, an article appeared in M. M. W. R. (Morbidity And Mortality Weekly Report) in which reference was made to 1,200 cases reported in the U.S. of a new high mortality disease, AIDS. More than 450 people had died due to this pathology, including people with Kaposi’s Sarcoma, drug addicts who abused injections, infections by some opportunistic parasites such as protozoa, helminths, fungi, bacteria and viruses, which reduce the resistance of these individuals leading to acute immunodeficiency syndrome and in homosexual and bisexual individuals, and some Haitian immigrants, which caused great alarm throughout the world.